2017
DOI: 10.1038/s41598-017-16137-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of skin colour on the experience of ownership in the rubber hand illusion

Abstract: Racial prejudice is associated with a fundamental distinction between “us” and “them”—a distinction linked to the perceived overlap between representations of the self and others. Implicit prejudice has been shown to reduce the intensity of White individuals’ hand ownership sensation as induced by the Rubber Hand Illusion (RHI) with dark rubber hands. However, evidence for this link to implicit prejudice comes from self-report questionnaire data regarding the RHI. As an alternative, we assessed the onset time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…Illusory ownership among White participants over a Black or White rubber hand [ 22 , 40 , 41 ] and a Black or White virtual body [ 20 , 23 , 24 ] has been replicated a number of times, and no differences were found between the subjective illusion of ownership between the virtual Black and White conditions. The same was found in [ 42 ] except that the time to onset of the illusion was longer for the Black rubber hand than the White. The Neutral and Positive conditions of our experiment provide a further replication of these findings.…”
Section: Discussionsupporting
confidence: 82%
“…Illusory ownership among White participants over a Black or White rubber hand [ 22 , 40 , 41 ] and a Black or White virtual body [ 20 , 23 , 24 ] has been replicated a number of times, and no differences were found between the subjective illusion of ownership between the virtual Black and White conditions. The same was found in [ 42 ] except that the time to onset of the illusion was longer for the Black rubber hand than the White. The Neutral and Positive conditions of our experiment provide a further replication of these findings.…”
Section: Discussionsupporting
confidence: 82%
“…A textural constraint is that if the rubber hand skin texture looks natural, the RHI is experienced more strongly than if it looks unnatural ( Haans et al, 2008 ) or does not match with the own skin color ( Farmer et al, 2012 ; Lira et al, 2017 ). Lira et al (2017) , for instance, recruited white participants and compared the inducibility of a RHI with a white and with a black rubber hand. What they found was that for the black rubber hand condition, there was a longer RHI induction time, lower SoO level and smaller proprioceptive drift than for the white rubber hand condition ( Lira et al, 2017 ).…”
Section: Sense Of Ownershipmentioning
confidence: 99%
“… Lira et al (2017) , for instance, recruited white participants and compared the inducibility of a RHI with a white and with a black rubber hand. What they found was that for the black rubber hand condition, there was a longer RHI induction time, lower SoO level and smaller proprioceptive drift than for the white rubber hand condition ( Lira et al, 2017 ).…”
Section: Sense Of Ownershipmentioning
confidence: 99%
“…This might also facilitate the perception of the other person as a whole, including the classification into an in- or out-group member. In fact, in previous studies that investigated sensorimotor processes when the other person’s body parts were seen from a first-person perspective (Farmer et al, 2012; Bufalari et al, 2014), no differences between dark- and light-skinned stimuli were found, at least not on an implicit level (but see Lira et al, 2017 for an exception). At the moment, these interpretations remain largely speculation.…”
Section: Discussionmentioning
confidence: 92%
“…For example, a bigger influence could be expected if we presented a real other person rather than an avatar, or a life-sized avatar rather than a small stimulus on a screen. Furthermore, in the case of the rubber hand illusion, no influence of skin color was found for proprioceptive drift (Farmer et al, 2012); yet with a presumably more sensitive measure (time-till-illusion, see Lira et al, 2017), a difference was evidenced. A further critique could be that the study was designed as an online study.…”
Section: Discussionmentioning
confidence: 98%